Influence Of Leadership, Work Discipline, And Training On Employee Performance Pt. Bevos Prima Center Jakarta - Sriayu Lumban Gaol; Agtovia Frimayasa (Sean Institute, 2023)
his study aims to be able to see leadership, work discipline and training on improving employee performance at PT. Bevos Prima Center, West Jakarta. This research is descriptive quantitative. Sampling of 50 people from a total of all employees at PT. Bevos Prima Center. The independent variables include leadership (X1), work discipline (X2), and training (X3), while the dependent variable is employee performance (Y). The research data was analyzed using multiple linear regression testing. The results of his research prove that Leadership, Work Discipline, and Training all significantly influence the performance of partial and simultaneous employees at PT. Bevos Prima Center Jakarta.